The early use of MDMA ('Ecstasy') in psychotherapy (1977–1985). (April 2018) - Passie, Torsten
3, 4-Methylenedioxymethamphetamine (MDMA), also known as ecstasy, was first synthesized in 1912 but first reached widespread popularity as a legal alternative after the much sought-after recreational drug 3, 4-methylenedioxy-amphetamine (MDA) was made illegal in 1970. Because of its benign, feeling-enhancing, and nonhallucinatory properties, MDMA was used by a few dozen psychotherapists in the United States between 1977 and 1985, when it was still legal. This article looks into the contexts and practices of its psychotherapeutic use during these years. Some of the guidelines, recommendations, and precautions developed then are similar to those that apply to psychedelic drugs, but others are specific for MDMA. It is evident from this review that the therapists pioneering the use of MDMA were able to develop techniques (and indications/counterindications) for individual and group therapy that laid the groundwork for the use of MDMA in later scientific studies. In retrospect, it appears that the perceived beneficial effects of MDMA supported a revival of psycholytic/psychedelic therapy on an international scale.